Aṡarul Madkhal Al-Ma’rifi Fī Tarqiyati Istī’ābi Al-Qawā’id An-Nahwiyyah Bil Madrasah Aṡ-Ṡānawiyyah Al-Ḥukūmiyyah Bi Mālāng - Ade Ruswatie (University of Darussalam Gontor, 2019)
Aṡarul Madkhal Al-Ma’rifi Fī Tarqiyati Istī’ābi Al-Qawā’id An-Nahwiyyah Bil Madrasah Aṡ-Ṡānawiyyah Al-Ḥukūmiyyah Bi MālāngAde RuswatiState Islamic Institute of Purwokertoaderuswatie@iainpurwokerto.ac.idAbstract Grammar is one of the important subjects for second graders of the Islamic and Arabic Sciences class in the third Islamic high school in Malang East Java, as it is a basis for building language proficiency. And understanding them requires the attractive educational process. Education can only be successful using educational approaches, or methods that are identical to the conditions of students or the educational material. Its teaching has been characterized since the establishment of this division that the students' understanding of the grammatical rules is weak. Based on this issue, the researcher experimented with one of the Arabic language teaching entrances, which is the knowledge entrance to know its effect in promoting its absorption. This research aims to know the application of teaching grammatical rules with the knowledge entrance and know its effect in promoting the absorption of grammatical rules for second graders of the Islamic and Arabic Sciences class. This research uses the experimental approach based on the quantitative approach, with the experience of teaching subjects from the grammatical rules subject to the cognitive approach while and in the traditional way at another time. After completing the teaching of each topic, the researcher conducted the post-test with 20 students. In this research, the researcher obtained the result: (1) Begin teaching grammatical rules on the basis of the cognitive entrance from the rules to the examples so that the researcher presents the rules and then sets examples on them. The exercises consciously apply the rules; (2) The knowledge entrance has a positive effect in promoting the understanding of grammatical rules for the second-grade pupils of Islamic and Arabic Sciences class, and because this approach takes into account linguistic competence and is concerned with it.Keywords: cognitive entrance, upgrade understanding of grammatical rulesأثر المدخل المعرفي في ترقية استيعاب القواعد النحويةبالمدرسة الثانوية الحكومية بمالانجأدي روسواتيالجامعة الحكومية الإسلامية فورواكارتوaderuswatie@iainpurwokerto.ac.idالملخصإن مادة القواعد النحوية إحدى المواد المهمة لتلاميذ الصف الثاني لشعبة العلوم الإسلامية والعربية في المدرسة الثانوية الإسلامية الثالثة بمالانج جاوا الشرقية، حيث أنها أساس في بناء الكفاية اللغوية. واستيعابها يحتاج إلى العملية التعليمية الجذابة. ولا يمكن أن يحصل التعليم على النجاح إلا باستخدام المداخل التعليمية أو الطرق أو الأساليب المطابقة بأحوال الدارسين أو المادة التعليمية. وقد اتصف تعليمها منذ تأسيس هذه الشعبة بأن استيعاب التلاميذ للقواعد النحوية ضعيف. وبناء على هذه القضية، قامت الباحثة بتجربة مدخل من مداخل تعليم اللغة العربية وهو المدخل المعرفي لمعرفة أثره في ترقية استيعابها. يهدف هذا البحث إلى معرفة تطبيق تعليم القواعد النحوية بالمدخل المعرفي ومعرفة أثره في ترقية استيعاب القواعد النحوية لتلاميذ الصف الثاني لشعبة العلوم الإسلامية والعربية. يستخدم هذا البحث المنهج التجريبي على أساس المدخل الكمي بتجربة تعليم الموضوعات من مادة القواعد النحوية بالمدخل المعرفي في حين وبالطريقة التقليدية في حين آخر. وبعد الانتهاء من تعليم كل موضوع ، قامت الباحثة بالاختبارات البعدية بعددهم 20 تلميذا. في هذا البحث، حصلت الباحثة على النتيجة: (1) يبتدئ تعليم القواعد النحوية على أساس المدخل المعرفي من القواعد إلى الأمثلة بحيث تعرض الباحثة القواعد ثم تضرب الأمثلة عليها وبعد انتهاء شرح القواعد والأمثلة، تنتقل الباحثة إلى التدريبات الأولية تحقيقا لفهم التلاميذ، ومن هدف هذه التدريبات تطبيق القواعد بشكل واع (2) إن للمدخل المعرفي أثرا إيجابيا في ترقية استيعاب القواعد النحوية لتلاميذ الصف الثاني لشعبة العلوم الإسلامية والعربية هذا ولأن هذا المدخل يراعي الكفاية اللغوية ويهتم بها.الكلمات الأساسية: المدخل المعرفي، ترقية استيعاب القواعد النحوية